Effects of Pesticides and Fungicides Used on Grapevines on the Mealybug Predatory Beetle Nephus ’boschianus’ (Coccinellidae, Scymnini) - Walton, V.M.; Pringle, K.L. (South African Journal of Enology and Viticulture, 2017)
The effects of frequently used grapevine insecticides and fungicides on adults of the predatory beetle Nephus ’boschianus’ of vine mealybug, Planococcus ficus (Signoret), were determined under laboratory conditions. When applied as cover sprays the pesticides chlorpyrifos, endosulfan, cypermethrin, chlorfenapyr and mercaptothion were very toxic to the predator, whilst the fungicides penconazole, fosetyl-Al, mancozeb and an insecticidal soap plus oil mixture were harmless. These results suggest that the insecticides may be harmful to a biological control system where N. ’boschianus’ populations were dominant during the season. The three fungicides and the soap plus oil mixture, however, should be compatible with biological control by N. ’boschianus’.